Association of anaesthesia technique with 30-day primary graft patency after open lower limb revascularization: retrospective cohort study. Issue 3 (3rd June 2022) - Ke, Janny Xue Chen; Flexman, Alana M.; Schwarz, Stephan K. W.; MacDonald, Shaun; Prabhakar, Christopher
Abstract: Background: The relationship between anaesthetic technique and graft patency after open lower limb revascularization is unclear. The aim of this study was to evaluate the association between 30-day graft patency after elective infrainguinal bypass and anaesthetic technique (regional anaesthesia (RA, i.e. neuraxial and/or peripheral nerve blockade) compared with general anaesthesia (GA)). Methods: Patients who underwent elective infrainguinal bypass in the 2014–2019 National Surgical Quality Improvement Program Vascular Procedure Targeted Lower Extremity Open data set were included. Excluded patients were those under 18 years old, those who did not receive RA or GA, and/or had an international normalized ratio of 1.5 of greater, a partial thromboplastin time more than 35 s, or a platelet count less than 80 × 10 9 /L. The primary outcome was primary graft patency without reintervention. The relationship between anaesthetic technique and patency was analysed with multivariable logistic regression. Results: Included were 8893 patients with a mean(s.d.) age of 68(11) years and 31.5 per cent female. Within the cohort, 7.7 per cent ( n  = 688) patients received RA only, 90.4 per cent ( n  = 8039) GA only, and 1.9 per cent ( n  = 166) both GA and RA. In the RA-only group, 91.7 per cent (631 of 688) received neuraxial anaesthesia. The primary patency rate was 93.2 per cent (573 of 615) for RA only, and 91.5 per cent (6390 of 6983) for GA only (standardized mean difference, 0.063). RA was not associated with a higher rate of patency compared with GA (adjusted OR, 1.16; 95 per cent c.i., 0.83 to 1.63; P  = 0.378). Conclusion: There was no association between anaesthetic technique and 30-day graft patency after elective infrainguinal bypass surgery. Further prospective studies would be useful to study the impact of anaesthesia technique on important patient-centred outcomes such as long-term patency and non-home discharge. Abstract : Graft patency after revascularization is associated with higher quality of life scores and is an important patient-centred outcome. We evaluated the association between 30-day graft patency after elective infrainguinal bypass surgery and anaesthetic technique (regional anaesthesia (neuraxial and/or peripheral nerve blockade) compared with general anaesthesia). Multivariable logistic regression did not show an association between anaesthetic technique and 30-day graft patency.